Scanning Electron Microscopy Study of Drilling Cuttings in Tomsk Oblast Sites; IOP Conference Series: Materials Science and Engineering; Vol. 272 : Earth science - Klimova (Mekh) A. A. Alyona Andreevna; Azarova S. V. Svetlana Valerievna; Yazikov Y. G. Yegor (Egor) Grigoryevich; Matveenko I. A. Irina Alekseevna (2019, 2019)
Title screen